Alterations in the inflammatory markers of the Tumor Necrosis Factor system in overweight and obese children and adolescents - Heloísa Marcelina da Cunha Palhares; Adriana Paula da Silva; Janaíne Machado Tomé; Marcos Vinícius da Silva; Virmondes Rodrigues Júnior; Flávia Alves Ribeiro; Marília Matos Oliveira; Elvi Cristina Rojas Fonseca; Ianessa Arantes Valle; Maria de Fátima Borges (PLoS ONE, 2025)
Objective This study analyzed the association between cardiometabolic risk markers and the tumor necrosis factor system in overweight and obese children and adolescents. Methods This cross-sectional study included 201 overweight (n =  65), obese (n =  96), and eutrophic (n =  40) children and adolescents aged 5 to 19 years. Clinical markers (body mass index, percentage of body fat, waist circumference, systolic and diastolic blood pressures) and laboratory parameters (glucose, insulin, total cholesterol and fractions, triglycerides, homeostasis assessment of insulin resistance index [HOMA-IR], leptin, tumor necrosis fator-α [TNF-α], soluble TNF receptors [sTNFR1 and sTNFR2], soluble Tumor necrosis factor-Related Apoptosis-Inducing Ligand [sTRAIL]) were evaluated. Results Serum TNF-α levels did not differ significantly between the participant groups, while the serum concentrations of sTNFR1 were higher in the obesity group, compared with those in the eutrophic and overweight groups. Regarding sTNFR2, there was no significant difference between the three study groups. Serum sTRAIL concentrations were higher in the eutrophic group compared with those in the overweight and obesity groups. We observed a positive correlation between sTNFR1 and body mass index, waist circumference, triglycerides, glucose and leptin levels. There was also a negative correlation between sTRAIL and body mass index, waist circumference, LDL cholesterol, glucose and HOMA-IR levels. Conclusions Inflammatory changes involving the TNF system (sTNFR1, sTRAIL) that correlate with obesity are present since childhood, indicating the need for early intervention in order to avoid cardiometabolic complications in adulthood.